Penerapan Metode Demonstrasi pada Pembelajaran IPA Siswa Kelas IV SDN 55/I Sridadi - Aina Wirda; Dandi Kurniawan; Amelia Murba; Syahrial Syahrial; Silvina Noviyanti (AS-SABIQUN, 2022)
This study aims to describe the application of the demonstration method in science learning for fourth grade students of SDN 55/I Sridadi. This research is a qualitative research. The informants of this study were fourth grade teachers. Data collection techniques used are observation, interviews, and documentation. Data analysis uses data reduction steps, data display, and drawing conclusions. Based on the results of observations made in class IV SDN 55/I Sridadi, the demonstration method is very appropriate to use for science learning. Teachers and students have been able to carry out the stages of implementing learning using the demonstration method, so that the learning process goes well. The interaction between teachers and students, students and students looks good. In addition, students can interact and really understand the material. However, in the learning process there are several obstacles experienced by the teacher. Among them are limited learning resources, learning tools, learning media, situations that are often not easy to manage and limited time. Based on the results of the study, it was concluded that the implementation of the demonstration method in science learning at SDN 55/I Sridadi had been carried out quite well, as evidenced by the presence of some of the steps of demonstration activities that had been carried out well by the teacher, such as preparing and conditioning students to study, taking attendance, praying and motivating students, conveying learning objectives and materials, to evaluation activities.